(3RGO GdeSjQ aj YdGL GdHhGSjQs - (3GdbhUhfj , TeS GdOjf eMeO Hf eMeO Hf eMeO Hf HOQ GdOjf GdbhUhfj,J (B931 (3g` s ((3eMeO Hf CMeO GdfTQJi GdceGd s)
(3ChdgG (B:s
(3bGd TjNfG GdbhUhfi fMeO Gddge jG MGaX GdUMI Ydi gPg GdCHOGf hHYO agPg QSGdI dWjaI JJYdb HGdYdg GdeYQha HGdHhGSjQ s
(3BNQgG (B:s
(3hEPG Ob SYa GdfNd hBNP ef eGFg TF LjO hGdbi Ydjg ai MGd WHNg cGf Cbhi ai JbhjI GdYVh s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdChdis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B260s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs